Contrast-Induced Nephropathy: Pathogenesis and New Therapeutic Options for Prevention. (November 2015) - Ortega, Luis M.; Harmouch, Imad; Nayer, Ali
Abstract : Contrast-induced nephropathy is a common cause of inpatient and outpatient acute renal failure. The pathogenesis is complex adding difficulty to its management. Several preventive measures that involved the use of intravenous fluids and oral agents have been implemented in human studies with heterogeneous results because of the disparity in defining changes in glomerular filtration rate after renal injury. New preventive techniques based on the pathogenesis of contrast-induced nephropathy are being applied to human subjects with preliminary good outcomes. Future randomized trials will give us the opportunity to elucidate its benefits.